Improving patient understanding and outcomes in myelodysplastic syndromes - An animated patient guide to MDS with visual formats of learning. (2022) - Sallman, David A.; Bejar, Rafael; Montalban-Bravo, Guillermo; Kurtin, Sandra E.; List, Alan F.; Garcia-Manero, Guillermo; Nimer, Stephen D.; O'Connell, Casey L.; Schaar, Dale; Butchko, Janice; Iraca, Tracey; Searle, Stephanie
Abstract: Objectives: Patient education resources that address barriers to health literacy to improve understanding and outcomes in myelodysplastic syndromes (MDS) are limited. The aim of this study was to evaluate the impact and outcomes benefits of An Animated Patient's Guide to Myelodysplastic Syndromes (MDS) cancer educational modules (which includes the 'You and MDS' website and YouTube hosted resources) related to MDS education, awareness, understanding and health outcomes. Methods: This was a retrospective study of learner feedback, metrics, and utilization data from July 2018 to August 2021. We evaluated audience reach (number of visit sessions, unique visitors, page views) and calculated top views by media type (animation, expert video, patient video, and slide show) and top retention videos from the modules. We also assessed the educational impact and utilization through learner feedback surveys. Results: During the study period, 'You and MDS' had 233, 743 views worldwide of which 104, 214 were unique visitors and 78, 161 (or 76% unique visitors) were from the United States. Of these, 61% were patients; 29% family members or caregivers; 5% were healthcare providers and 5% represented other groups. Most popular topics viewed among the animations were "Understanding Myelodysplastic Syndromes (MDS)" (40, 219 views), "Managing and Treating MDS" (19, 240 views), "Understanding Erythropoiesis" (17, 564 views.) The most popular expert videos viewed were "What is iron overload, and how it is treated?" (20, 310 views), "How serious a cancer is MDS? What is the prognosis for MDS?" (8, 327 views), "What is MDS?" (3, 157 views). Of participants who completed the online feedback survey, ≥ 95% reported improved knowledge gains and commitments to change. Conclusions: MDS patients using 'You and MDS - An Animated Patient's Guide to MDS' and its visual formats of learning represented a wide U.S. and global learner audience. This MDS educational resource had a significant impact on improved understanding among patients, families, and caregivers. Continued efforts should be made to provide patient-effective resources that address health literacy, improve patient understanding, and address educational needs that respond to the concerns of patients to achieve better quality of life and improved health outcomes in MDS.